2021
DOI: 10.1021/acs.jpclett.1c01840
|View full text |Cite
|
Sign up to set email alerts
|

Porphyrin Binding and Irradiation Promote G-Quadruplex DNA Dimeric Structure

Abstract: Nucleic acid sequences rich in guanines can organize into noncanonical DNA G-quadruplexes (G4s) of variable size. The design of small molecules stabilizing the structure of G4s is a rapidly growing area for the development of novel anticancer therapeutic strategies and bottom-up nanotechnologies. Among a multitude of binders, porphyrins are very attractive due to their light activation that can make them valuable conformational regulators of G4s. Here, a structure-based strategy, integrating complementary prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 62 publications
(104 reference statements)
2
12
1
Order By: Relevance
“…On the other hand, in the intermediateand low-Q regions, the intensity I(Q) reflects the higher-order structure arising from the reversible multimerization process of G4 units. In particular, the contribution of Tel22 multimers is quite visible, as a clear deviation below Q < 1 nm −1 in Figure 1, where the scattering intensity of a solution of Tel22 monomers at DNA concentration C = 0.5 mM (data taken from Reference [28]) is compared with that of the present study. It is worth noting that the monomeric sample was prepared in such a way to rule out the presence of possible aggregates (see the Methods section).…”
Section: Small-angle X-ray Scatteringmentioning
confidence: 58%
See 3 more Smart Citations
“…On the other hand, in the intermediateand low-Q regions, the intensity I(Q) reflects the higher-order structure arising from the reversible multimerization process of G4 units. In particular, the contribution of Tel22 multimers is quite visible, as a clear deviation below Q < 1 nm −1 in Figure 1, where the scattering intensity of a solution of Tel22 monomers at DNA concentration C = 0.5 mM (data taken from Reference [28]) is compared with that of the present study. It is worth noting that the monomeric sample was prepared in such a way to rule out the presence of possible aggregates (see the Methods section).…”
Section: Small-angle X-ray Scatteringmentioning
confidence: 58%
“…Also in the high-Q region, where the SAXS signal is dominated by the form factor, the interpretation of the experimental data deserves great care. In a previous study [28], we found the form factor of Tel22 monomers in solution to be well described by that of a hard cylinder (HC). In this case the topology of Tel22 consists of a mixture of antiparallel and hybrid conformers, however, an increase of concentration above ≈ 1 mM drives a progressive shift toward the parallel (propeller) state, with concomitant decrease of the anti-parallel and hybrid forms [30,31,32,33].…”
Section: Small-angle X-ray Scatteringmentioning
confidence: 91%
See 2 more Smart Citations
“…Within this context, a considerable body of research has been carried out to investigate the structural properties of different G4-forming DNA sequences [18][19][20][21] and how they are affected by small ligands. 1,[22][23][24][25] However, little is known about the dynamical features of G4s, an aspect that should play a relevant role given their transient nature. In the case of proteins and duplex DNA, the sub-nano-and nanosecond dynamics has been already linked to both structural and functional aspects.…”
Section: Introductionmentioning
confidence: 99%